Analisa Sistem Informasi Haji Pintar pada Kementrian Agama Kota Bekasi - Nuning Khanif Aulia (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2025)
This research was conducted at The Ministry of Religion of Bekasi where there is a special division to serve Hajj Program for prospective Hajj at Bekasi City. The benefits of this research is every employees who working in The Ministry of Religion of Bekasi and prospective pilgrims user can using this information system of Haji Pintar with a efficiently by the time. There is two division that get attention in this research between Hajj and Umroh Services Agency also the employees that working inside The Ministry of Religion of Bekasi. Information System of Haji Pintar will be used very useful from doing the process of sign up in online way so there is no need to visit again. Beside that make it easier for every employees to processing data entry into the haji pintar database. In the future all the things of people is already familiar with the method of hajj sign in by online with this application to make it easier for valid providing information regarding the hajj program.